The Benefits and Challenges of Solar Photovoltaic (PV) Business in Pertamina’s Gasoline Station: Focused on Energy Transition, Sustainability & Green Investment - Paluseri, Andi Hendra; Kaihatu, Thomas S.; Christian, Timotius Febry (Universitas Mercu Buana, 2025)
Objectives: As the world shifts towards green energy solutions, PT Pertamina (Persero), Indonesia's state-owned energy company, is in a unique position to lead by integrating Solar Photovoltaic (PV) systems into its extensive network of gasoline stations. As per now, Pertamina has built Solar Photovoltaic (Solar PV) in 358 gasoline stations not only in Indonesia but also in East Timor. This research paper explores the benefits and challenges associated with the implementation of Solar PV. The study highlights key benefits in energy transition, sustainability & green investment. However, several challenges arise.Methodology: Descriptive and qualitative methods were used. The study focuses on Solar PV in gasoline station in Pertamina area. In-depth interviews and participant observations were used to collect data.Finding: reveal a significant green energy production, reduction in carbon footprint, making it a sustainable energy business for Pertamina. Nonetheless, the challenges of high upfront costs, space limitations, and potential maintenance and operation challenges are also identified.Conclusion: Solar PV systems offer significant potential benefits for Pertamina’s gasoline stations, including green energy production, environmental sustainability, cost reduction, and enhanced energy security. Despite challenges related to high upfront costs, space limitations, and regulatory barriers, Pertamina’s leadership in renewable energy positions the company to overcome these obstacles and drive the adoption of solar PV technology across its gasoline station network. By investing in solar PV systems, Pertamina can play a critical role in advancing Indonesia’s renewable energy goals, reducing carbon emissions, and demonstrating its commitment to sustainability. Through strategic partnerships, policy advocacy, and scalable deployment models, Pertamina has the potential to become a leader in solar PV adoption at gasoline stations, contributing to a cleaner and more sustainable energy future for Indonesia.